2015
DOI: 10.1007/s00704-015-1437-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal characteristics of the large-scale moisture flux transport over the Arabian Peninsula

Abstract: The relationship between the lower tropospheric (1000 to 850 hPa) large-scale moisture flux transport and the precipitation over the Arabian Peninsula (AP), on a seasonal basis, using the NCEP-NCAR gridded dataset for the 53-year period , is investigated. The lower tropospheric moisture flux divergence occurs due to the Hadley cell-based descending air over the AP, as well as due to the presence of Somali jet in dry season (June to September) for the southern (≤22°N) AP domain, leading to significantly reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Based on the above discussion, we anticipate that considering NAO and ENSO as leading patterns would be enough to account for most of the variability over MENA region in the winter season. Similarly ENSO and ISM appear to have significant contribution in summer season over MENA (Abualnaja et al, ; Almazroui et al, ; Athar, ; Athar & Ammar, ). The ISM plays a significant role in strengthening of the coastal precipitation both in West Africa and over the Horn of Africa to the east by affecting the Intertropical Convergence Zone (ITCZ; i.e., the upward branch of Hadley circulation) and the Somali jet.…”
Section: Model Data and Methodologymentioning
confidence: 96%
See 1 more Smart Citation
“…Based on the above discussion, we anticipate that considering NAO and ENSO as leading patterns would be enough to account for most of the variability over MENA region in the winter season. Similarly ENSO and ISM appear to have significant contribution in summer season over MENA (Abualnaja et al, ; Almazroui et al, ; Athar, ; Athar & Ammar, ). The ISM plays a significant role in strengthening of the coastal precipitation both in West Africa and over the Horn of Africa to the east by affecting the Intertropical Convergence Zone (ITCZ; i.e., the upward branch of Hadley circulation) and the Somali jet.…”
Section: Model Data and Methodologymentioning
confidence: 96%
“…It has been discussed in several studies that the NAO is one of the primary modes of atmospheric variability in the North Atlantic sector that largely impacts the climate of Europe and MENA (Abualnaja et al, ; Athar, ; Barlow et al, ; Hurrell, ; Yu & Zhou, ). ENSO and ISM (or simply Indian monsoon) have also been reported as important modes of variability that impact MENA climate (Abualnaja et al, ; Athar, ; Athar & Ammar, ; Chakraborty et al, ; Wanner et al, ). Wanner et al () and Athar () have shown that both the NAO and ENSO are the prominent modes of variabilities that are essential to be considered while discussing Northern Hemisphere winter climate, especially the climate of AP region.…”
Section: Model Data and Methodologymentioning
confidence: 99%
“…27 However, the low-level divergent anomalies due to the descending Hadley cell and the existence of the Somali Jet over the southern peninsula tend to suppress the rainfall in the region. 28 Most studies are conducted using observational datasets, and the details of the mechanism connecting summertime peninsula rainfall with ENSO are not explored. The current study investigates the summer rainfall mechanism in relationship with ENSO by using a 15-member ensemble of simulations with the Saudi-King Abdulaziz University (KAU) AGCM 29 (see Methods).…”
Section: Introductionmentioning
confidence: 99%
“…where CC is the coefficient of the Spearman correlation and d i is the difference in rank between the paired values. Furthermore, characteristics of spatial distribution of moisture transport were studied, by computing the horizontal divergence of vertically integrated moisture flux between 1,000 and 850 hPa using methods described in previous studies (Athar and Ammar, 2016). The spatial moisture transport distribution is studied for positive and negative seasonal DTR years of the region, following You et al (2016).…”
Section: Methodsmentioning
confidence: 99%